2005
DOI: 10.1097/00001813-200501000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Biweekly docetaxel and vinorelbine with granulocyte colony-stimulating factor support for patients with anthracycline-resistant metastatic breast cancer

Abstract: This phase II trial evaluated the efficacy and toxicity of vinorelbine 25 mg/m2 plus docetaxel 60 mg2/m administered on day 1, every 2 weeks with granulocyte colony-stimulating factor support (G-CSF, 5 microg/kg/day, days 3-7) as primary prophylaxis in patients with histologically confirmed metastatic breast cancer (MBC) and previously treated with anthracyclines in the adjuvant or in the first-line setting. A total of 48 patients received 352 cycles (median 8, range 2-10). All patients were included in the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In addition, literature data have reported interesting results, probably because of a synergistic effect, when using the 2 drugs in combination. [22][23][24][25][26][27][28][29][30][31][32] The efficacy results observed in the present study are in line with those of previous experiences with the same regimen as reported in Table 4. [22][23][24][25][26][27][28][29][30][31][32] Our data report a 51% ORR with a 17% CR rate and a median survival of 14 months in a series of patients with visceral metastases and heavily pretreated once again confirming the value of the combination of DCT and VNR in the treatment of MBC.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, literature data have reported interesting results, probably because of a synergistic effect, when using the 2 drugs in combination. [22][23][24][25][26][27][28][29][30][31][32] The efficacy results observed in the present study are in line with those of previous experiences with the same regimen as reported in Table 4. [22][23][24][25][26][27][28][29][30][31][32] Our data report a 51% ORR with a 17% CR rate and a median survival of 14 months in a series of patients with visceral metastases and heavily pretreated once again confirming the value of the combination of DCT and VNR in the treatment of MBC.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, noteworthy is that no toxic deaths have been recorded. These data are definitely more favorable as compared with those of other experiences, [22][23][24][25][26][27][28][29][30][31][32] particularly with respect to the study by Kornek et al 23 that reported an high incidence of peripheral neurotoxicity (42%) and hematological toxicity with septic complications notwithstanding the use of G-CSF. It is very likely Treating Metastatic Breast Cancer that the differences in safety profile are ascribable to the different treatment schedule since we delivered VNR only on day 1 of each cycle, instead of days 1 and 8 as reported in other experiences.…”
Section: Discussionmentioning
confidence: 66%
“…Most of these studies delivered the two drugs same day, without growth factor, which led to high RRs but also high toxicity [28–31]. Because of significant neutropenia seen in combining docetaxel and vinorelbine, subsequent studies incorporated growth factor to maintain dose intensity, but still included overlapping same-day dosing of the two drugs [32, 33]. Despite the addition of filgrastim in these trials, neutropenia remained a common toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Other common grade III/IV toxicities included thrombocytopenia, anemia, and nausea/vomiting, all with less than a 7% incidence of grade III/IV events. When docetaxel was combined with other drugs every 2 weeks, toxicity profile changed accordingly (Table 4) [22,[29][30][31][32][33][34][35]. Vinorelbine-containing and irinotecan-containing regimens had more myelosuppressive and gastrointestinal toxicity, respectively (Table 4).…”
Section: Discussionmentioning
confidence: 99%